Impact of Talent Management on Organizational Performance with Political Skills as a Moderating Variable - Andi Batary Citta; Hikmah Hikmah; Sukmatica Slamet; Ulfa Dwi Yanti (IECON: International Economics and Business Conference, 2023)
The purpose of this study is to have an in-depth analysis of the relationship between Talent Management and Organizational Performance. As well as knowing in detail the role of political skills in the organization. A quantitative approach was used in this study. The data for this study were collected from PT Bank Sulselbar through a survey method via a questionnaire, sampling using porpusive sampling with a total sample of 80 respondents. The data analysis technique in this study uses Moderated Regression Analysis (MRA), with tools (SPSS) which will provide clear results using validity and reliability testing, data normality test and classical assumption test. The results are in the positive direction and meet the research objectives, which reveal that there is a positive relationship between talent management and subsequent organizational performance, Political skills moderate the relationship between talent management and organizational performance.